Quem vai falar da e com a juventude LGBTT na escola pública?: um estudo junto a uma EMEF de São Paulo à luz do pensamento fenomenológico - Fachim, Felipe Luis (2017)
The present work proposes an investigation on the LGBTQ theme in a Municipal School of Elementary Education (EMEF), located in a peripheral region in the North Zone of the city of São Paulo, in order to build a project about sexual and gender education, regarding the LGBTQ theme for teachers, students and school staff and analyze its developments. This is a qualitative research, of an interventionist nature, within the framework of an academic master's degree, within the group of Research in Educational Practices and Attention to the Family, School and Community (Ecofam), of the Graduate Program in Educational Psychology PUC-SP. Its main objective is to intervene and investigate the psychoeducational processes related to gender and sexuality, with regard to the LGBTQ theme, in the public school. The specific objectives are: (I) Participate in the psychoeducational processes related to the theme gender, sexuality, in the LGBTQ perspective, together with two instances: students and professionals responsible for the education of the students and for the formation of the school; (II) Co-construct a place in the school where this theme can be discussed. With a methodology that dialogues existential phenomenology and feminist proposals of knowledge construction, we intend to analyze our intervention, fruit of a year and a half of face-to-face work with teachers and adolescents of EMEF, organized in experiences reports constellated in the paradigm of the hermeneutical circle. The constellations found are: (I) Morro Grande adolescents: reflections on adolescence; who are the LGBTQ teenagers; humiliation and families from the teen perspective; (II) The educators of Morro Grande: reflections on educators; who are the LGBTQs who appear in the research in a psychoeducational context; humiliation and violence regarding school practices; (III) In search of a conclusive route to intervention - resignificances in the discourse of adolescents and teachers; analysis of what potentiates the intervention or not. The results point to: (I) discrepancies between adolescents and the concept of adolescence created by the psychoeducational discourse, being that the latter invisibilizes the former; (II) the school, among other institutions, exerts, by means of “straightterrorist” acts, violence on people who do not fit into the order constructed by the "Straight Mind"; (III) reflective attitudes, coconstructed in the community’s terms, have proved potent in the re-signification of the meanings of the themes surrounding the LGBTQ population, which, in turn, is increasingly in a condition of vulnerability and exclusion in the context exposed. Who is going to talk about and with the LGBTQ youth in public school?